EDUKASI PERAN LINGKUNGAN PENDERITA TB DALAM UPAYA MENINGKATKAN KEPATUHAN PENGOBATAN TB PARU - Siti Aisyah; Vony Nofrika; Niko Prasetya; Anna Rohana (Jurnal Pengabdian IKIFA, 2024)
Even though much progress has been achieved in TB control in Indonesia, there are still many challenges, including the increase in TB co-infection, management weaknesses and continuity of funsing for TB control programs. One of the reasons for this is patients’ non-compliance with treatment. Non-compliance with treatment will result in a high rate of treatment failure for pulmonary TB sufferers. Directly Observed Therapy Short course (DOTs) is a treatment strategy for detection and cure of tuberculosis. Medication monitoring (PMO) is one of the strategies of DOTs. The aim of Community Service (PkM) activities in Penggilingan Village is to educate the role of the environment for TB sufferers in an effort to increase treatment compliance for pulmonary TB patients. The PkM activity was attended by 32 residents in the Penggilingan Village area. The results of the PkM activities found that the counseling carried out was able to increase knowledge of the role of the TB sufferer’s environment in an effort to increase compliance with pulmonary TB treatment.